VARIATIONS OF INDONESIAN TRHOUGHFLOW TRANSPORT IN MALUKU AND HALMAHERA SEA RELATED TO THE OCCURRENCE OF EL NINO SOUTHERN OSCILLATION - Hasti Amrih Rejeki; B Betsi; Yogi Muhammad Andariwan (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2021)
ABSTRACTMaluku and Halmahera Sea are the entry paths for the Indonesian Throughflow (ITF). This study examined the variation of their current speed, current direction, and transport during the ENSO phases on La Nina in 2010-2011 and El Nino in 2015-2016. The data used were the Marine Copernicus reanalysis data of u and v components of current velocity at 155 m and 266 m of depth. The data were processed by using GrADS to see the direction and speed of the current as well as by calculating the ITF transport. During La Nina, both at 155 m and 266 m of depths were found the eddy patterns. When El Nino occurred, the direction of currents in Maluku Sea was different from La Nina conditions, while the direction of currents in Halmahera Sea had no differences. Current velocity in both oceans at each depth was lower during El Nino than La Nina. The condition of ITF transport in the Maluku Sea during La Nina was dominated by southward movement with a smaller value than during El Nino which generally moved northward meanwhile in the Halmahera Sea had the opposite condition.Keywords: current speed, current direction, ENSO, ITF, transport